2023
DOI: 10.1111/bph.16170
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide signalling in neurodegenerative diseases

Abstract: The gaseous neurotransmitter hydrogen sulfide (H2S) exerts neuroprotective efficacy in the brain via post‐translational modification of cysteine residues by sulfhydration, also known as persulfidation. This process is comparable in biological impact to phosphorylation and mediates a variety of signalling events. Unlike conventional neurotransmitters, H2S cannot be stored in vesicles due to its gaseous nature. Instead, it is either locally synthesized or released from endogenous stores. Sulfhydration affords bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 183 publications
0
11
0
Order By: Relevance
“…Although the pathological role of H2S in neurodegenerative disorders remains controversial 36 , excessive H2S is linked to neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS) 36 37 38 . The concentration of H2S in the cerebrospinal fluid was maintained at a high level in patients with sporadic ALS 37 , and the disease-enhancing effect of H2S as a glial-released inflammatory factor was confirmed in several studies using an animal model of ALS 37 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathological role of H2S in neurodegenerative disorders remains controversial 36 , excessive H2S is linked to neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS) 36 37 38 . The concentration of H2S in the cerebrospinal fluid was maintained at a high level in patients with sporadic ALS 37 , and the disease-enhancing effect of H2S as a glial-released inflammatory factor was confirmed in several studies using an animal model of ALS 37 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, S-sulfinylation and S-sulfonylation of DJ-1, which lead to its inactivation [22,170,173], modulates Parkin S-nitrosylation, enhancing its activity and altering mitochondrial quality control with a predicted impact on PD pathogenesis [170,178]. Adapted from [47]. Ageing is considered a major risk factor for all NDDs, which are commonly characterized by aggregation and accumulation of misfolded oxidized proteins.…”
Section: Redox-ptms and Their Crosstalk In Nddsmentioning
confidence: 99%
“…H 2 S and related RSS play important roles in cell signaling and homeostasis, with direct impacts in a wide array of cellular processes including angiogenesis, inflammation, vasorelaxation, and regulation of oxidative stress. Furthermore, imbalances in endogenous H 2 S production are associated with different deleterious conditions, including neurodegenerative diseases, hypertension, diabetes, and liver cirrhosis. For example, increasing evidence has shown that endogenous H 2 S production within the brain decreases in individuals with Parkinson’s disease, and exogenous H 2 S treatment has been shown to prevent further neurodegeneration in rodent models. , In addition to the direct role of H 2 S in many of these pathways, small molecule and protein persulfides formed from oxidative posttranslational modification of Cys residues also play key roles in H 2 S biological action. , This rapid growth of established and speculated roles of H 2 S in human health, as well as the molecular level appreciation for possible signaling pathways involving RSS, has propelled both the need and development of innovative chemical approaches to measure and manipulate H 2 S in biological contexts.…”
Section: Introductionmentioning
confidence: 99%